Benefits of infant massage for newborns and infants: Integrative review (Research, Society and Development, 2023)
The objective of this study was to identify in the literature the benefits of applying infant massage to preterm newborns, full-term newborns and infants. An integrative literature review was carried out based on a search in PubMed, BVS Saúde, Web of Science and Scopus databases, using as strategies the keywords indexed in DeCS: newborn, massage and physiotherapy and in MeSH: “ infant”, “newborn”, “massage”, “Physical Therapy Specialty”. Original articles, published in English, Portuguese or Spanish, between the years 2014 and 2019 were included. Data analysis was carried out in a descriptive way, for this, a table was used, containing: citation, year of publication, country of origin, study participants, method and main results. The level of evidence was identified based on the study design. Regarding the study design, four were systematic reviews, four were randomized clinical trials, ten non-randomized controlled trials (quasi-experiment) and five were qualitative or descriptive studies. Within the level of evidence, eight studies were classified as strong, ten as moderate, and five as weak. Thus, there is a need to develop protocols to perform infant massage interventions in preterm and full-term newborns and infants. We suggest conducting randomized clinical trials on the application of the technique in these populations, with larger samples and study time, in order to obtain better evidence.